Firefly combinatorial test list generator for IoT systems - Alsewari, Abdulrahman A.; A. BaHomaid, Ameen; Rassem, Taha H.; Kamal Z., Zamli; Posten, Robin (Faculty of Computer Systems & Software Engineering, 2018)
A common problem in ioT systems is the large number of the combinations of hardware, operational, and software configurations that required to be tested to ensure the IoT systems are free of bugs.